Eumelanic coloration and age interact to influence breath rate following a boldness test in urban pigeons - Sophie Dupont; Emmanuelle Baudry; Pauline Juette; Julien Gasparini (Global Journal of Ecology - Peertechz Publications, 2020)
The rapid urbanization of the past decades has forced numerous species to adapt to their new environments over a very restricted time scale. Previous studies suggested that individuals living in urban areas have specific characteristics as compared to those living in rural areas. In feral pigeon populations (Columba livia), individuals living in cities are more melanic than those living in less urbanized areas. In this study, we tested whether the degree of eumelanin-based coloration in pigeons reflects certain adaptations to urban areas such as boldness and tolerance to stress. Hence, we examined the relationship between eumelanin-based coloration and three variables of boldness (arrival to a new food source, arrival latency, and flight distance) and tolerance to stress (breath rate). Our results show that the eumelanin-based coloration of individuals is not correlated with the boldness variables, but tends to be positively related to breath rate in adults. Therefore, eumelanin-based coloration could reflect the capacity of adult individuals to manage stress in an urban environment, but not the boldness. The higher frequency of eumelanic pigeons observed in cities might thus be due to urban selective forces that favor individuals with a higher response to stress than bolder individuals.